Passionflower in the treatment of opiates withdrawal: a double blind and randomized controled trial - Seyed Hamzeh Hosseini; Azin Khazaeli; Mousa Khani; Shahin Akhondzadeh (Institue of Medicinal Plants, ACECR, 2002)
Clonidine-base detoxification has been utilized as the main protocol for several years However, detoxification with clondine has its limitation, including lack of efficacy for mental symptoms. Accumulating evidence shows the efficacy of Passifloru incurnata extract in management of anxiety. In our continuing study of traditional medicines, which have neurotropic effects, the use of this plant reported an anxiolytic effect, which can be evaluated as an adjuvant agent in the detoxification of opiates by clonidine. We presented the results from a double-blind randomized controlled trial of clonidine plus passiflora extracts vs., clonidine plus placebo drop in the outpatient detoxification of 65 opiates addicts. A total of 65 opiates addicts were randomly assigned to treatment with passiflora extract plus clonidine tablet or clonidine tablet plus placebo drop during a 14 days, double-blind clinical trial. All patients met the DSM-IV criteria for opioid dependence. The fixed daily dose was 60 drops for passiflora extract and the maximum daily dose for clonidine was 0.8 mg. This trial medication was given three times per day in divided doses. The severity of the opiate withdrawal syndrom was measured in days 0.1.2.3.4.7 and 14 using SOWS (Short Opiate Withdrawal Scale). Both protocols were equally effective in treating the physical symptoms of withdrawal syndrom. However, passionflower plus clonidine group showed a significant superiority over the clonidine alone in the management of mental symptoms. These results suggested that passiflora extract may be an effective adjuvant agent in the management of opiate withdrawal. However, a larger study to confirm our results is warranted.